Shaking and pushing skyrmions: Formation of a nonequilibrium phase with zero critical current - Felix Rucker; Alla Bezvershenko; Denis Mettus; Andreas Bauer; Markus Garst; Achim Rosch; Christian Pfleiderer (Proceedings of the National Academy of Sciences, 2026)
In three-dimensional chiral magnets, skyrmions are line-like objects oriented parallel to the applied magnetic field. The efficient coupling of magnetic skyrmion lattices to spin currents and magnetic fields permits their dynamical manipulation. Here, we explore the dynamics of skyrmion lattices when slowly oscillating the field direction by up to a few degrees on millisecond timescales while simultaneously pushing the skyrmion lattice by electric currents. The field oscillations induce a shaking of the orientation of the skyrmion lines, leading to a phase where the critical depinning current for translational motion vanishes. We measure the transverse susceptibility of MnSi to track various depinning phase transitions induced by currents, oscillating fields, or combinations thereof. An effective slip–stick model for the bending and motion of the skyrmion lines in the presence of disorder explains main features of the experiment and predicts the existence of several dynamical skyrmion lattice phases under shaking and pushing representing phases of matter far from thermal equilibrium.